(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the integration of modern teaching methods in mathematics education. It delves into the significance of incorporating innovative approaches to enhance student engagement, critical thinking, and problem-solving skills. The paper highlights the importance of active learning, technology-based tools, and project-based learning in fostering a dynamic and effective mathematics classroom.